2019
DOI: 10.1038/s41598-019-46261-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gene Expression Profiles of Breast Cancers in Indian Women

Abstract: Breast cancer is the most common cancer among women globally. In India, the incidence of breast cancer has increased significantly during the last two decades with a higher proportion of the disease at a young age compared to the west. To understand the molecular processes underlying breast cancer in Indian women, we analysed gene expression profiles of 29 tumours and 9 controls using microarray. In the present study, we obtained 2413 differentially expressed genes, consisting of overexpressed genes such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 103 publications
2
28
0
Order By: Relevance
“…We confirmed that 5 genes, including COL11A1 , GFAP , FGF5 , CD300LG , and IGFL2 , were co-expressed with WT1 . In agreement with our results, the high expressions of WT1 , COL11A1 , and FGF5 in BC tumors have also been reported in previous literatures ( Huang, Wang & Yang, 2018 ; Li, Kong & Zou, 2017a ; Malvia et al, 2019 ). WT1 overexpression could promote ERK1/2 phosphorylation and thus decreasing E-cadherin expression and enhance EMT (epithelial-to-mesenchymal transition) ( Han et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed that 5 genes, including COL11A1 , GFAP , FGF5 , CD300LG , and IGFL2 , were co-expressed with WT1 . In agreement with our results, the high expressions of WT1 , COL11A1 , and FGF5 in BC tumors have also been reported in previous literatures ( Huang, Wang & Yang, 2018 ; Li, Kong & Zou, 2017a ; Malvia et al, 2019 ). WT1 overexpression could promote ERK1/2 phosphorylation and thus decreasing E-cadherin expression and enhance EMT (epithelial-to-mesenchymal transition) ( Han et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…As these findings align with the sequencing data obtained in our study, its expression level in GC is yet to be clarified. Through a study of ADAMTS1 in breast cancer, its expression level was found to be low [ 18 21 ]. However, another study found that it can promote breast cancer metastasis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In depth, we explored HDAC2's potential target that might be involved in ARAP1-AS1-regulated BC development. And PLIN1, a recently identified anti-tumor gene in BC [23,24] was chosen to be research object since UCSC suggested that HDAC2 might be one of potential regulators of it. First of all, we uncovered that inhibition of HDAC2 gave rise to the mRNA and protein expressions of PLIN1 in both MCF7 and MDA-MB-231 cells ( Figure 3A,B).…”
Section: Plin1 Is Negatively Regulated By Hdac2 At Transcriptional Levelmentioning
confidence: 99%